Rancangan Aplikasi Sistem Informasi Administrasi SPP TK Ikhsan Kamil Berbasis Desktop - Feni Kristanti; Kiky Zulkifli (Asosiasi Dosen Akuntansi Indonesia, 2026)
This study aims to design a desktop-based tuition fee (SPP) administration information system for TK Ikhsan Kamil in Desa Tigasan, which still uses manual recording and is prone to errors, data loss, and delays in preparing financial reports. The development method used is the System Development Life Cycle (SDLC) with the Waterfall model, focusing on the stages of analysis, design, and testing without full implementation. This research also employs a mixed-method approach, combining qualitative methods through observation and interviews, and quantitative methods through the System Usability Scale (SUS) questionnaire to measure the usability level of the system design. The results of the study include business process analysis, use case design, activity diagrams, class diagrams, and interface designs covering student data management, teacher data management, tuition payment processing, payroll, and reporting. The designed system is expected to improve efficiency, accuracy, and transparency in administration management